1983
DOI: 10.1016/0014-5793(83)80204-x
|View full text |Cite
|
Sign up to set email alerts
|

Dependence on cyclic AMP of glucose‐induced inactivation of yeast gluconeogenetic enzymes

Abstract: and keywords not received

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1984
1984
1990
1990

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…The values obtained are similar to those previously published for stationary phase cells and acetate-grown cells of yeast (Thevelein, 19846). They also agree very well with those published by other workers for stationary phase cells (Van der Plaat, 1974;Purwin et al, 1982;Tortora et al, 1982Tortora et al, , 1983 with the exception of Mazon et al (1982) who found an increase of the estimated intracellular cAMP concentration from 0.3 PM to 1.2 WM.…”
Section: Discussionsupporting
confidence: 93%
“…The values obtained are similar to those previously published for stationary phase cells and acetate-grown cells of yeast (Thevelein, 19846). They also agree very well with those published by other workers for stationary phase cells (Van der Plaat, 1974;Purwin et al, 1982;Tortora et al, 1982Tortora et al, , 1983 with the exception of Mazon et al (1982) who found an increase of the estimated intracellular cAMP concentration from 0.3 PM to 1.2 WM.…”
Section: Discussionsupporting
confidence: 93%
“…In S. cerevisiae there is no evidence showing that K increases the cAMP levels. It is important to say at this point that we did not find any trehalase activation by 200 mM K + (Table 1) and that Tortora et al [13] utilize 100 mM potassium phosphate buffer pH 6.0 in the media before the addition of glucose to determine the CAMP-dependent glucose-induced inactivation of various yeast gluconeogenetic enzymes. These findings, together with the data in Table 1 and Figs.…”
Section: Discussionmentioning
confidence: 77%
“…Most experiments showing increases in cAMP levels (Maz6n et al, 1982;Tortora et a/., 1983;Franqois et a/., 1984) and the subsequent modification of FBPase (Mazbn el a/., 1982), trehalase (Franqois et a/., 1984) and various other enzymes (Tortora et a/., 1983;Franqois et a/., 1984;Caspani et al, 1985) have been done with glucose-grown cells collected at the stationary phase and suspended in a medium with K+. Thus, it was important to determine whether reversal of glucose-induced acidification was necessary to obtain the CAMP-dependent enzyme modification.…”
Section: R E S U L T Smentioning
confidence: 97%